CORRELATION OF HBA1C LEVELS OF PROLANIS PATIENTS WITH DIABETES MELLITUS TO MICROALBUMINURIA LEVELS AT KESUGIHAN I HEALTH CENTER - Nugrahaeni, Dian Rahma; Faizal, Imam Agus; Nugroho, Yusuf Eko (Jurnal Mitra Kesehatan, 2025)
Introduction : Chronic hyperglycemia and disorders of carbohydrate, fat, and protein metabolism are signs of a metabolic disease known as diabetes mellitus. The disease is caused by abnormalities in the secretion of insulin or the work of insulin. Higher HbA1C levels indicate uncontrolled diabetes mellitus, and in high-risk patients, long-term complications that can be fatal. The presence of albumin in the urine of people with diabetes mellitus causes a problem known as diabetic nephropathy. In a damaged glomerular condition, kidney leakage can occur which allows proteins, especially albumin, to seep into the urine. The purpose of this study was to find out whether there was a relationship between HbA1C levels of prolanis diabetic mellitus patients and microalbuminuria levels at the Kesugihan I Health Center. Method: This study used a cross-sectional description design, with a research sample of results from the HbA1C and microalbuminuria examination of prolanis patients at the Kesugihan I Health Center from January to March 2025, meeting the inclusion and exclusion criteria of 60 samples. Result: The Spearman correlation test for this study found a correlation value of -0.163 between HbA1C and microalbuminuria levels, with a p-value of 0.214. Conclusion: The conclusion of this study is that there is no correlation between HbA1C levels of prolanis patients with diabetes mellitus and microalbuminuria levels at the Kesugihan I Health Center.